2017
DOI: 10.2215/cjn.09330916
|View full text |Cite
|
Sign up to set email alerts
|

A Kidney Graft Survival Calculator that Accounts for Mismatches in Age, Sex, HLA, and Body Size

Abstract: Background and objectives Outcomes for transplants from living unrelated donors are of particular interest in kidney paired donation (KPD) programs where exchanges can be arranged between incompatible donor-recipient pairs or chains created from nondirected/altruistic donors.Design, setting, participants, & measurements Using Scientific Registry of Transplant Recipients data, we analyzed 232,705 recipients of kidney-alone transplants from 1998 to 2012. Graft failure rates were estimated using Cox models for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…Furthermore, we found that the burden of graft failure tends to be largest in the youngest age‐at‐transplantation quartile, decreasing with each quartile. This is consistent with prior research that has shown that the probability of graft failure is usually higher in younger kidney transplant recipients than in older recipients . We also found that the burden of graft failure is larger for living donor patients compared to all kidney transplant recipients, as transition probabilities estimated using SRTR data (Figure S4A,B) indicated that living donor patients were more likely to receive re‐transplants after graft failure, thus incurring additional costs in the event of graft failure.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we found that the burden of graft failure tends to be largest in the youngest age‐at‐transplantation quartile, decreasing with each quartile. This is consistent with prior research that has shown that the probability of graft failure is usually higher in younger kidney transplant recipients than in older recipients . We also found that the burden of graft failure is larger for living donor patients compared to all kidney transplant recipients, as transition probabilities estimated using SRTR data (Figure S4A,B) indicated that living donor patients were more likely to receive re‐transplants after graft failure, thus incurring additional costs in the event of graft failure.…”
Section: Discussionsupporting
confidence: 91%
“…spousal donation). An online calculator based on the SRTR data is available for estimating survival times where multiple LD options are available [56]. The key to appreciating waiting times is knowing the matchability score of the patient and understanding the local kidney offering scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Cumulate evidence from numerous observational studies [33]. Thus, recently published calculators for kidney graft survival include BMI in the risk model [34]. As a consequence, loss of body weight is recommended in renal transplant candidates [34,35].…”
Section: The Role Of Obesity In Kidney Transplantationmentioning
confidence: 99%
“…Thus, recently published calculators for kidney graft survival include BMI in the risk model [34]. As a consequence, loss of body weight is recommended in renal transplant candidates [34,35]. Obviously, many patients are unable to achieve significant weight loss from conventional measurements.…”
Section: The Role Of Obesity In Kidney Transplantationmentioning
confidence: 99%